1999
DOI: 10.1146/annurev.immunol.17.1.189
|View full text |Cite
|
Sign up to set email alerts
|

NATURAL KILLER CELLS IN ANTIVIRAL DEFENSE: Function and Regulation by Innate Cytokines

Abstract: Natural killer (NK) cells are populations of lymphocytes that can be activated to mediate significant levels of cytotoxic activity and produce high levels of certain cytokines and chemokines. NK cells respond to and are important in defense against a number of different infectious agents. The first indications for this function came from the observations that virus-induced interferons alpha/beta (IFN-alpha and -beta) are potent inducers of NK cell-mediated cytotoxicity, and that NK cells are important contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
1,451
2
18

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,886 publications
(1,502 citation statements)
references
References 242 publications
26
1,451
2
18
Order By: Relevance
“…2C) that are strong NK-cell stimulators [31,32], we examined whether NK cell-activating agents may delay tumor development in vivo through an NK cellmediated mechanism. We therefore treated clinically unapparent l-myc mice with CpG-ODN 1668 for several weeks.…”
Section: Nk-cell Activation Delays Lymphoma Development In K-myc Micementioning
confidence: 99%
“…2C) that are strong NK-cell stimulators [31,32], we examined whether NK cell-activating agents may delay tumor development in vivo through an NK cellmediated mechanism. We therefore treated clinically unapparent l-myc mice with CpG-ODN 1668 for several weeks.…”
Section: Nk-cell Activation Delays Lymphoma Development In K-myc Micementioning
confidence: 99%
“…In addition to cytotoxic properties, NK cells have immunoregulatory functions. Through the expression of cell surface molecules and the secretion of cytokines such as IFN-g, they directly modulate macrophages, B and T lymphocyte and DC functions [11,12,14,15]. Consequently, in addition to a protective role in anti-tumor and antiviral immunity, it is now suggested that NK cells may play a role in inflammation, autoimmune disorders and hematopoietic and solid organ transplantation [11].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The KIR receptors can be grouped into three distinct lineages based on the configuration of the extracellular immunoglobulin (Ig)-like domains. 3 The first lineage comprises two Ig domain-containing KIRs with D0-D2 configuration (KIR2DL4 and 2DL5), the second lineage comprises three Ig domain containing KIRs with D0-D1-D2 configuration (KIR3DL1-3 and 3DS1) and the third lineage comprises two Ig domain containing KIRs with D1-D2 configuration (KIR2DL1-3 and 2DS1-5).…”
Section: Introductionmentioning
confidence: 99%